Iron/Polyindole-based Electrocatalysts to Enhance Oxygen Reduction in Microbial Fuel Cells. (1st February 2016) - Nguyen, Minh-Toan; Mecheri, Barbara; Iannaci, Alessandro; D'Epifanio, Alessandra; Licoccia, Silvia
Graphical abstract: Highlights: Electrocatalysts based on iron, polyindole, and carbon nanotubes (FePc/PID/CNTs). FePc/PID/CNTs as catalysts at cathodes of microbial fuel cells (MFCs). High and stable power generation. Cost reduction with respect to Pt-based MFCs. Abstract: Electrocatalysts derived from polyindole (PID) and iron phthalocyanine (FePc) on carbon nanotubes (CNTs)/carbon Vulcan (C) have been synthesized and used as cathodes in Microbial Fuel Cells (MFCs). The morphology characterization performed by scanning electron microscopy (SEM) indicated a good dispersion of polyindole and FePc on carbon surface for all samples. The electrochemical activity towards oxygen reduction reaction (ORR) has been assessed by cyclic voltammetry (CV), showing enhanced performance of CNTs-based composites in comparison with C-based composites. Rotating disk voltammetry experiments demonstrated that ORR at FePc/CNTs and FePc/PID/CNTs catalysts led to more positive half-wave potential values and higher kinetic current density values compared to that of reference Pt/C; the best ORR performance was displayed by FePc/PID/CNTs sample. In MFCs operating with sodium acetate in phosphate buffer solution, FePc/PID/CNTs cathode allows achieving a maximum power density of 799 ± 41 mW m −2 and a current density of 3480 ± 83 mA m −2 that are higher than those achieved with commercial Pt/C cathode (646 ± 25 mW m −2 and 3011 ± 84 mA m −2, respectively). The long-term MFC operation conducted for 700 h indicates a stable performance of FePc/PID/CNTs cathode, demonstrating its potential ability to substitute platinum catalyst for ORR in MFCs.